PERANCANGAN ALMARI KABINET SISTEM VEENER - Dwi Agus Susilo; Ravendra Duansyah; Gunawan Mohammad (SULUH: Jurnal Seni Desain Budaya, 2020)
The result of the veener application cabinet design design is the use of wood basic components from unproductive pieces of furniture. If the rest of the furniture is used only in the home industry such as tofu makers, building brick makers. Even though a lot of this wood cut material comes from the furniture home industry in Jepara. This environmental problem will be discussed in this study, namely how to design renewable furniture products with scrap materials from furniture production that currently have disturbed the living environment An innovative form of creativity is a solution taken, namely designing a cupboard with a variety of design choices. 1) observing how many pieces of wood left over from furniture in Krapyak village, 2) exploring the ability of human resources to process wood scraps into sheets of boards, 3) designing designs that match the conditions of the raw materials that have been formed, 4) executing the selected designs into furniture products in the form of cupboards. This process will build a positive foundation that the remaining pieces of wood from furniture processing can be recycled to be processed into products that have resale value.